Correction: Sainz et al. Analysis of Thioredoxins and Glutaredoxins in Soybean: Evidence of Translational Regulation under Water Restriction. Antioxidants 2022, 11, 1622 - María Martha Sainz; Carla Valeria Filippi; Guillermo Eastman; José Sotelo-Silveira; Omar Borsani; Mariana Sotelo-Silveira (MDPI AG, 2023)
In the original publication [...]